2015
DOI: 10.1039/c5cp01128k
|View full text |Cite
|
Sign up to set email alerts
|

Controllable fabrication of immobilized ternary CdS/Pt–TiO2 heteronanostructures toward high-performance visible-light driven photocatalysis

Abstract: Immobilized TiO2 nanotube arrays (NTAs) co-modified with Pt and CdS nanoparticles were fabricated by using the combination of photoreduction and chemical bath deposition methods. XRD, SEM, TEM, XPS, UV-Vis and EDX methods were employed to characterize the microstructure and composition of samples, and the results showed that CdS and Pt NPs were uniformly deposited on the surface of TiO2 nanotubes. The CdS/Pt/TiO2 NTAs exhibited a much higher photocatalytic activity compared to pure TiO2 NTAs and binary CdS (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In multicomponent modified TiO 2 , as compared to one-component modified TiO 2 , different components can be combined with one another such that the catalyst has different degrees of improvement in light absorption performance and electron-hole separation efficiency. Gao et al [273] used photoreduction deposition and chemical bath deposition to prepare Pt and CdS nanoparticles on co-modified TiO 2 nanotubes. The decomposition rate of methyl orange dye with Pt and CdS co-modified TiO 2 nanotubes reached 91.9% under visible light.…”
Section: Semiconductor Compoundmentioning
confidence: 99%
“…In multicomponent modified TiO 2 , as compared to one-component modified TiO 2 , different components can be combined with one another such that the catalyst has different degrees of improvement in light absorption performance and electron-hole separation efficiency. Gao et al [273] used photoreduction deposition and chemical bath deposition to prepare Pt and CdS nanoparticles on co-modified TiO 2 nanotubes. The decomposition rate of methyl orange dye with Pt and CdS co-modified TiO 2 nanotubes reached 91.9% under visible light.…”
Section: Semiconductor Compoundmentioning
confidence: 99%
“…It has been found that there are many methods for fabricating noble metal/sulde composites, such as the microwave assisted reduction method, the photoreduction coupled water bath method, and the in situ deposition method. [21][22][23][24][25][26] However, the above mentioned methods have some disadvantages, such as a complicated operation, high cost, and can be difficult to control. Therefore, it is highly desirable to nd a simple and fast technique to obtain noble metal/sulde composites.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Fujishima and Honda in 1972, using TiO 2 as a photocatalyst became widely concerned . However, there were two key barriers to restrict the wide application of TiO 2 photocatalyst . On the one hand, TiO 2 is a wide‐band‐gap semiconductor with a wide bandgap of ∼3.2 eV, which limits the absorption of visible light.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were two key barriers to restrict the wide application of TiO 2 photocatalyst . On the one hand, TiO 2 is a wide‐band‐gap semiconductor with a wide bandgap of ∼3.2 eV, which limits the absorption of visible light. On the other hand, the recombination rate of photogenerated electrons and holes in TiO 2 was rather high to lead to seriously lowered photocatalytic performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation